(untitled) - Moore, William T. (New York, 2001)
Praise for Real Options and Option-Embedded Securities "Whether you are deciding which capital projects to undertake, determining how to finance those projects, or managing and controlling risks arising from your investment and financing decisions, you confront options within the modern firm. Real Options and Option-Embedded Securities is noteworthy in that it offers a comprehensive treatment of pricing and strategic applications of options throughout the firm. This includes designing and valuing option-embedded securities issues, accounting for flexibility in capital project analysis, and employing options within a firm's risk management program. This book should prove quite useful to practicing financial managers and business students alike."-Clifford W. Smith Jr., Louise and Henry Epstein Professor, University of Rochester "In this uncertain and fast-changing economic environment, corporations and consultants draw heavily on the concept of real options to quantify and direct strategy. For instance, we value start-up ventures as options, and Real Options and Option-Embedded Securities provides a detailed guide to identifying and valuing options such as these. My only complaint about the book is that it wasn't available when I studied options in my MBA program! Nicely done. I highly recommend it."-Anton Griessner, Senior Consultant, Deloitte Consulting "This book accomplishes two things I didn't think possible. It presents a comprehensive yet understandable treatment of the challenging field of option pricing, and it offers a unified approach to the use of options in solving problems in corporate finance. The book delivers! I heartily recommend it to practitioners and students of modern finance."-Darla Moore, President, Rainwater, Inc. www.wileyfinance.com
Keywords: Sự lựa chọn (Tài chính),Options (Finance)